Determination of optimal load in the Wingate Anaerobic Test is not depend on number of sprints included in mathematical models - Michalik, Kamil; Smolarek, Marcin; Ochmann, Bartosz; Zatoń, Marek (Frontiers in Physiology, 2023)
Determining the optimal load (OPTLOAD) in measuring mechanical peak power output (PPO) is important in assessment of anaerobic fitness. The main goals of this study were: 1) to examine estimated optimal load and PPO based on a force-velocity test and 2) to compare the PPO from the previous method with the Wingate Anaerobic Test (WAnT). The study involved 15 academic male athletes, aged 22.4 ± 2.3 (years), height 178.9 ± 6.8 (cm), and body weight 77.9 ± 12.2 (kg). They performed the 30-s WAnT (7.5% of body weight) during the first visit to the laboratory. Second to fourth session included a force-velocity test (FVT) involving three, 10-s all-out sprints. A randomized load ranging from 3 to 11 kg was used in each session for FVT. The OPTLOAD and PPO were computed using quadratic relationships based on power-velocity (P-v) and power-percent of body weight (P-%BM) and including three, four, five and nine sprints from FVT. The results showed non-difference in OPTLOAD [13.8 ± 3.2 (%BM); 14.1 ± 3.5 (%BM); 13.5 ± 2.8 (%BM); 13.4 ± 2.6 (%BM)] executed at three, four, five, and nine sprints (F3,56 = 0.174, p = 0.91, η2 = 0.01). The two-way ANOVA revealed that PPO were similar between tested models (P-%BM vs. P-v) independently from the numbers of sprints (F3,112 = 0.08, p = 0.99, η2 = 0.000). Moreover, the PPO measured in the WAnT (870.6 ± 179.1 W) was significantly lower compared with in P-v model (1,102.9 ± 242.5–1,134.2 ± 285.4 W) (F4,70 = 3.044, p = 0.02, η2 = 0.148). In addition, the PPO derived from P-%BM model (1,105.2 ± 245.5–1,138.7 ± 285.3 W) was significantly higher compared with the WAnT (F4,70 = 2.976, p = 0.02, η2 = 0.145). The findings suggest the potential utility of FVT for assessment of anaerobic capacity.